2008
DOI: 10.2166/wst.2008.388
|View full text |Cite
|
Sign up to set email alerts
|

NH4+ ad-/desorption in sequencing batch reactors: simulation, laboratory and full-scale studies

Abstract: Significant NH4-N balance deficits were found during the measurement campaigns for the data collection for dynamic simulation studies at five full-scale sequencing batch reactor (SBR) waste water treatment plants (WWTPs), as well as during subsequent calibrations at the investigated plants. Subsequent lab scale investigations showed high evidence for dynamic, cycle-specific NH4+ ad-/desorption to the activated flocs as one reason for this balance deficit. This specific dynamic was investigated at five full-sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Moreover, according to the previous studies, the sorption amount of NH 4 + ‐N (mass of the adsorbed NH 4 + ‐N to 1 g MLSS) onto the sludge flocs was only 0.07–0.2 mg g −1 suspended solids (SS) . In that case, based on the results of other studies, only 0.21–0.6 mg L −1 of NH 4 + ‐N was adsorbed onto the sludge flocs in this study, which further proved the steady variation of NH 4 + ‐N (Figure a). Higher NH 4 + ‐N concentration showed no promotion for adsorption.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, according to the previous studies, the sorption amount of NH 4 + ‐N (mass of the adsorbed NH 4 + ‐N to 1 g MLSS) onto the sludge flocs was only 0.07–0.2 mg g −1 suspended solids (SS) . In that case, based on the results of other studies, only 0.21–0.6 mg L −1 of NH 4 + ‐N was adsorbed onto the sludge flocs in this study, which further proved the steady variation of NH 4 + ‐N (Figure a). Higher NH 4 + ‐N concentration showed no promotion for adsorption.…”
Section: Resultssupporting
confidence: 86%
“…In the sorption assays, the concentration of NH 4 + ‐N remained almost constant during the whole period of experimentation (Figure a), demonstrating that the anoxic sludge had low or no adsorption of NH 4 + ‐N. It was previously reported that the sorption of NH 4 + ‐N was based on ion‐exchange, which was significantly influenced by other cations (e.g., Ca 2+ , Na + , K + , Fe 2+ , and Fe 3+ ) adsorbed onto the negatively charged bacterial cell walls . In the sorption assays, the content of these cations in the supernatant indeed decreased (Figure S1 and S2, Supporting Information), indicating the sorption of these ions onto the sludge.…”
Section: Resultsmentioning
confidence: 68%
“…Based on a series of lab-tests a cycle-specific NH þ 4 ad-and desorption processes in SBR activated sludge samples could be found within the range of 1.0-2.5 mg NH þ 4 per 10 g MLSS (Schwitalla et al 2008). To describe the cycle-specific NH þ 4 ad-and desorption processes in SBR activated sludge systems, two fractions SNHs (free NH þ 4 ions) and XNH (floc adsorbed NH þ 4 ions) are introduced replacing the original SNH fraction.…”
Section: Model For Lag-phasesmentioning
confidence: 99%
“…However, Nielsen (1996) had found a purely chemical NH þ 4 ad-and desorption to activated sludge flocs at conventional activated sludge plants. Subsequent lab-scale analysis revealed cycle-specific NH þ 4 ad-and desorption processes in SBR activated sludge samples within the range of 1.0-2.5 mg NH þ 4 per 10 g MLSS (Schwitalla et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation